Geopolitical choice of the national security ideology: the example of Ukraine - Oleksiy Kriukov; Tomasz Michalski (Przegląd Geopolityczny)
The purpose of the article is to clarify the correlation that exists between the ideology pursued by the government and the state of national security. National security is considered in the context of the state's domestic and foreign policy and its efforts to maintain social stability and development. The directions of state activity, in turn, depend on the geopolitical orientation, which is a derivative of civilizational choice. The analysis made is illustrated with examples from Ukraine, which has made a pro-Western geopolitical and civilizational reorientation.